Pengaruh Pengawasan Fungsional Dan Akuntabilitas Publik Terhadap Kinerja Pemerintah Daerah (Studi Empiris Pada SKPD Provinsi Riau) - Yulia Petra Harvianda; Raja Adri Satriawan; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
One important element of good government is the absence of public accountability, in addition to transparency, rule of law, and regulations. Therefore, supervision is an essential element in the process of government management, has a strategic role for the realization of public accountability in the governance and development. One is the performance of the government on regional work units.This study aims to determine the effect of Functional Control and Public Accountability to the Local Government Performance In SKDP Riau Province. Respondents in this study are numbered 38 people. The type of data used is the data in the form of the data subject with the method of data collection using questionnaires. The method of data analysis used in this study is a multiple linear regression (multiple regression) with the help of Statistical Product and Service Solution (SPSS) software version 19.0.The results of this study showed both partial and simultaneous monitoring of functional variables significantly influence the performance and accountability of local government, because in the world of government, every part of government must be right people, which has competence in accordance with the predetermined qualification. While the coefficient of determination shows all variables of independently functional oversight and public accountability used in this study provide a contribution of 15.2% to the dependent variable of local government performance. While the remaining 84.8% describe other independent variables were not included in this study.Keywords: functional oversight, public accountability and performance of local government.